Evaluating engineering thinking in undergraduate engineering and liberal arts students. (4th May 2019) - Bell, Sarah; Chilvers, Andrew; Jones, Liz; Badstuber, Nicole
ABSTRACT: This study explored if it is possible for liberal arts students to develop engineering professional competencies without detailed engagement with the engineering sciences. Students on a Bachelor of Arts and Sciences programme were compared with their undergraduate peers in Civil Engineering. A new method for evaluating such competencies was developed. Two one-hour individual problem-solving exercises were devised to assess capabilities against 14 criteria, based on the Institution of Civil Engineers' Competency framework for professional development (2011 The BASc cohort's scores for each criterion improved notably from the start of term to the end. This cohort rated their capabilities more highly at the end of term and was more satisfied with the answers they gave. Engineering students showed a slight decline in performance against the criteria. Self-evaluation in this group revealed a smaller increase in perceived capability but increased dissatisfaction. Both cohorts felt more anxious about the assignment at the end of the term. PBL environments can improve student competence in attributes associated with professional engineering. The scope of the study is constrained by the small cohort but the findings and evaluation method provide the basis for further development, including detailed statistical evaluation and validation of the evaluation instrument.